2021
DOI: 10.3390/antiox10111689
|View full text |Cite
|
Sign up to set email alerts
|

Separation, Purification, Structure Analysis, In Vitro Antioxidant Activity and circRNA-miRNA-mRNA Regulatory Network on PRV-Infected RAW264.7 Cells of a Polysaccharide Derived from Arthrospira platensis

Abstract: To investigate the structure of Arthrospira platensis polysaccharide (PAP) (intracellular polysaccharide) and the antioxidant activity of the first component of PAP (PAP-1) on pseudorabies virus (PRV) -infected RAW264.7 cells. The PAP was separated and purified by the Cellulose DE-52 chromatography column and Sephacryl S-200 high-resolution gel column to obtain PAP-1. The antioxidant activity and regulation of PAP-1 on PRV-infected RAW264.7 cells of circRNA-miRNA-mRNA network were investigated by chemical kit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Many studies have found that appropriate molecular modifications or structural modifications can lead to new activities or the further enhancement of the original activities of polysaccharides [31]. The selenization modification of polysaccharides has become a focus of attention.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that appropriate molecular modifications or structural modifications can lead to new activities or the further enhancement of the original activities of polysaccharides [31]. The selenization modification of polysaccharides has become a focus of attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, a small proportion of A. platensis polysaccharides obtained by different extraction methods were monosaccharides (Ai et al ., 2023). Numerous studies have shown that polysaccharides in A. platensis are mainly composed of glucose, mannose and rhamnose; they also contain a small part of monosaccharides such as arabinose, fucose and galactose (Chen et al ., 2020b; Cao et al ., 2021; Cai et al ., 2022a). Monosaccharide compositions vary with growth environments and extraction methods.…”
Section: Functional Ingredients In Arthrospira Platensismentioning
confidence: 99%
“…Interestingly, fungal extracellular polysaccharides as a promising source of nutrients have attracted an increasing focus [ 1 ]. Previous reports revealed that marine fungal extracellular polysaccharides possessed structural diversity and potential biological activities, such as an Aspergillus versicolor extracellular polysaccharide composed of residues of (1→6)-linked α-D-glucopyranose, slightly branched by single α-D-mannopyranose residues [ 2 ], Hansfordia sinuosae extracellular polysaccharide mainly composed of mannose residue possessed antitumor activity [ 3 ], a polysaccharide from Phoma herbarum YS4108 having immunomodulatory effects on T cells and dendritic cells [ 4 ], an extracellular polysaccharide from the mangrove-associated Fusarium oxysporum, and the polysaccharide derived from Arthrospira platensis with antioxidant activity [ 5 , 6 ]. However, more marine fungal polysaccharides still need to be investigated to understand their structural features and mechanisms of action in depth.…”
Section: Introductionmentioning
confidence: 99%